Exploring the Applications and Advancements of Copper and Copper Alloys in Modern Manufacturing Processes - T.R. Vijayaram (International Journal of Industrial and Product Design Engineering, 2024)
For industrial uses, copper represents one of the greatest technical materials offered. This review paper discusses on the history of copper and copper alloys, salient features of wrought and cast copper alloys, physical and chemical characteristics of copper alloys, classification of copper alloys, design for manufacturing of copper alloys, mechanical properties of cast copper alloys, role of lead in copper alloys and applications of copper alloys in various engineering industries. Copper continues to be an important factor in the development of technology, with applications ranging from its conventional use in electrical wiring and plumbing to its more recent use in additive manufacturing and nanotechnology. The article focuses on the latest findings and advancements in copper-based materials research, including alloy creation, processing methods, and their effects on improving manufacturing efficiency, sustainability, and performance. It also looks at how recycling and environmental effects are related to copper materials, highlighting how crucial sustainable practices are to the manufacturing sector. This article lays the groundwork for future developments and applications by offering insightful information about how copper and its alloys are changing in the context of contemporary manufacturing through a thorough analysis of the literature and case studies.
Keywords: Copper; classification; copper alloys; copper development association; manufacturing